Student engagement, context, and adjustment: Addressing definitional, measurement, and methodological issues. (June 2016) - Fredricks, Jennifer A.; Filsecker, Michael; Lawson, Michael A.
Abstract: The goal of this special issue is to examine relationships among context, student engagement, and adjustment. We begin by describing the reasons for the increased popularity of student engagement in research, policy, and practice, and then describe how researchers in the field define and study this construct. Next, we outline some of the issues and challenges around the definitions, measurement, and analytic techniques that have been used in prior research. Finally, we provide a short overview of the papers in this special issue highlighting their theoretical frameworks, methodologies, and analytical techniques by which many of the challenges outlined in this introduction are addressed. The overall findings of these papers come from samples in Finland, Korea, and the United States. Highlights: Reasons for the increased popularity of the concept of engagement are outlined. Limitations with prior theoretical and empirical research on engagement are outlined. A description of papers in the special issue is presented.